La(Zn1−2xMnxCux)SbO: A new diluted magnetic semiconductor isostructural to 1111-type iron pnictide superconductors. (9th February 2018) - Zhao, Yao; Wang, Kai; Guo, Shengli; Fu, Licheng; Gu, Yilun; Zhi, Guoxiang; Xu, Lingxiu; Cui, Qi; Cheng, Jinguang; Wang, Hangdong; Chen, Bin; Ning, F. L.
Abstract: A new diluted magnetic semiconductor La(Zn1−2 x Mn x Cu x )SbO in bulk form has been successfully synthesized. Spins and carriers are introduced by co-doping Mn and Cu into Zn sites of the parent semiconductor LaZnSbO. Doping Mn or Cu alone does not induce magnetic ordering. Only when Mn and Cu are co-doped, can the system undergo a ferromagnetic transition below the Curie temperature . The ferromagnetic La(Zn1−2 x Mn x Cu x )SbO shares the same two-dimensional crystal structure as that of the 1111-type iron pnictide superconductor . A relatively large coercive field of is observed from the iso-thermal magnetization measured at 2 K.